Wybrane cechy osobowooeci kobiet trenujacych sporty walki - Burdzicka-Wolowik, J.; Góral-Radziszewska, K. (Polish Journal of Sport and Tourism, 2014)
Contemporary women are more and more independent nowadays and emancipation of women is also visible in sports. The aim of the study was to present certain personality traits of female athletes training selected combat sports. The authors claim that taking up the aforementioned activity is an attempt at overcoming stereotypical attitude to a social role of women. The analysis of results revealed psychological profiles of female athletes. Material and methods. The research included women aged 17 to 36 (N=199). The first group (N=94) consisted of athletes training boxing, judo, wrestling and taekwon-do, the majority of whom had a master sports class. The second group included women not training any sports (N=105). The research was conducted with the use of the following tools: Psychological Gender Inventory, Temperament Inventory, Eysenck Personality Questionnaire (EPQ-R), Creative Behaviour Questionnaire and personal questionnaire created by the authors. Conclusions. The analysis of the material showed that female athletes training combat sports contest traditional femininity since they have more personality traits traditionally attributed to men (high level of masculinity). High psychoticism of the athletes is also perceived as a tendency to break conventions. As highly non-conformist individuals, they live according to their own system of values training sports which are stereotypically treated as masculine. Combat sports are trained by women with low emotional and sensory reactivity, which gives them advantageous position in sports competition.